Subject and non-subject ex-situ focus in Dagbani. Issue 1 (8th January 2020) - Issah, Samual A.; Smith, Peter W.
Abstract : This paper offers a description and account of the patterns of ex-situ focus in Dagbani. We show that there are two syntactic strategies for creating ex-situ focus in the language, one involving A'-movement to the left periphery, and the second involving base generation in the left periphery combined with coreference to a resumptive pronoun. Furthermore, we argue that subjects are difficult to move from Spec, TP to Spec, CP in the left-periphery because of anti-locality, which creates a tension when trying to focus subjects, which are required to derivationally fill the specifier of both positions. We further show that what looks to be a two-way distinction between the behaviour of subjects and non-subjects in the language is in fact a three-way distinction between subjects that are focussed to a local left-periphery, subjects that are focussed to a non-local left-periphery, and non-subjects. These distinctions arise due to there being two methods for Dagbani to resolve the antilocality problem of subject movement, and so local subjects solve the problem differently to non-local subjects.